Corporate Social Performance and Use of Debt: an Examination of Australian Companies - Subba Reddy Yarram; Josie Fisher (Australasian Accounting, Business and Finance Journal, 2021)
This study examines whether the corporate social performance (CSP) activities of firms influence the structure of debt in the Australian context. Long-term debt is often associated with higher monitoring by lenders, which suggests that firms may benefit from using long-term debt strategically. Short-term debt arises from regular business dealings with a number of primary stakeholders such as customers, suppliers, employees and lenders. We propose in this study that businesses that are committed to improving CSP outcomes may reduce use of short-term debt contributing to building sustainable long-term relationships with the primary stakeholders. We therefore investigate whether firms that prioritise CSP favour long-term debt or short-term debt. Using a sample of Australian Securities Exchange (ASX) listed firms, this study finds that the level of CSP is not associated with long-term debt use, but there is a significant negative association between CSP and the short-term debt usage. This finding suggests that firms with stakeholder-friendly policies reduce their use of short-term debt rather than long-term debt. The reduced use of short-term debt helps resolve possible conflicts between the primary stakeholders and a firm, thus this study presents evidence supporting stakeholder theory and conflict-resolution hypothesis.
Keywords: Corporate social performance; Debt; Stakeholder theory.